Quantifying floodplain denitrification along the middle Mississippi River: novel incubation methods bound denitrification rates and landscape-scale nitrogen mitigation potential - Samberg, Stony S.; Brooks, Marjorie L.; Remo, Jonathan W. F.; Hamilton-Brehm, Scott D. (Frontiers in Freshwater Science, 2025)
Nitrate removal via microbial denitrification in floodplains is an important ecosystem service that can potentially help mitigate anthropogenic nitrogen inputs from rivers. However, floodplain denitrification estimates can vary by four orders of magnitude, making it difficult to quantify the social value of floodplain nitrogen mitigation potential. Constraining floodplain denitrification rates requires innovative experiments that mimic overland flooding of oxic water vs. infiltration of sometimes anoxic hyporheic waters to bound the rates. We incubated soils of varying textures and corresponding hydraulic connectivity from four field sites across the Dogtooth Bend of the middle Mississippi River, contrasting their varied rates of denitrification using novel deep injection compared to traditional surface delivery of oxic or anoxic river water. Averaged across all soil types, denitrification rates as nitrogen (N) gas production followed an anoxic-injection hierarchy of anoxic deep > anoxic surface > oxic deep > oxic surface treatments. Rates in sand ranged from 101 to 592 mg N/m2/day compared to diffusion-limited clay, which ranged from 166 to 448 mg N/m2/day. The chemical stoichiometry of nitrate (NO3-N) loss to N gain indicated apparent nitrification that replaced approximately 62% of N removed by denitrification even in anoxic treatments, modifying net rates for oxic-surface-injection vs. anoxic-deep-injection treatments to 31 to 176 (sand) and 81 to 162 mg N/m2/day (clay), respectively. Combining net denitrification bounds with the daily inundation exceedance probabilities for the 140 km2 of connected floodplain at Dogtooth Bend indicates, on average, between 70 and 385 tons of N may be removed annually from floodwater during the growing year. While the potential nitrogen removal equates to a small percentage ( ≤ 0.06%) of the river's nitrogen load, economically, the estimated monetary value of N mitigation is worth US$156–$4,106/ha/growing season compared to net profits for soybeans and corn of US$79 and US$88/ha/yr, respectively. Thus, N mitigation across the Dogtooth Bend could rival the agricultural use of floodplain lands.